A novel reutilization of ash from biomass gasification process: Feasibility and products improvement analysis. (1st May 2023) - Guo, Qianqian; Yan, Beibei; Hu, Yanjun; Guo, Xiang; Wu, Wenzhu; Cheng, Zhanjun; Chen, Guanyi; Hou, Li'an
Graphical abstract: Highlights: Reutilizing ash to gasification process was feasible. Ash played dual objective in improving gas product quality and adsorbing SO2 . Metals in ash promoted the Dry or/and Steam reforming and Water-gas reaction. The optimal condition of ash loading was 10 wt%. The regenerated ash behaved a higher fertilizer potential. Abstract: Due to the significant growth of the biomass gasification industry, management and disposal of ash has become one of the major environmental issues. This work proposed an innovative strategy that reutilizes ash into gasification process based on its potential catalysis to improve gas products. Reutilization of ash from corn straw (CS) air gasification in a downdraft fixed-bed gasifier was conducted for a feasibility analysis. The effect of ash loading rates (2 wt%, 5 wt%, 10 wt%, 15 wt%, and 20 wt%) on gasification performance were evaluated for an optimal condition analysis. Ash reutilization was proved to be feasible and able to achieve dual objective of improving gas product quality and reducing SO2 release. Results revealed that loading ash exhibited catalysis promoting CO formation, which correlated with the metal active sites provided by the ash and led to an improvement in dry or/and steam reforming. H2 production was also improved. These positive effects increased as ash loading rates increased, and maximum CO and H2 content (19.97 vol% and 15.72 vol%) were achieved at the ash loading rate of 10 wt%. Accordingly, the maximum LHV of gas products (6.47 MJ/Nm 3 ) and the minimum tar content (3.62 g/Nm 3 ) were obtained. While excess ash (loading rate > 10 wt%) showed unsatisfactory performance, even being far behind CS gasification without ash addition. Due to containing CaO, gasification ash showed SO2 capture capacity by forming CaSO4 . This reaction competed with the concurrent CaO carbonation, whereas the latter was the priority. The properties of by-products (regenerated ash) were evaluated for overall economic benefits, and the results indicated that it had a high fertilizer potential. These results seemed to be interesting and valuable for ash utilization and effective gasification.